Bilayer chlorophyll derivatives as efficient hole-transporting layers for perovskite solar cells. (23rd July 2019) - Li, Na; Dall'Agnese, Chunxiang; Zhao, Wenjie; Duan, Shengnan; Chen, Gang; Sasaki, Shin-ichi; Tamiaki, Hitoshi; Sanehira, Yoshitaka; Miyasaka, Tsutomu; Wang, Xiao-Feng
Abstract : Bilayer chlorophyll derivatives are examined as a hole-transporting layer for perovskite solar cells, leading to enhancement in device performance and stability. Abstract : Two synthetic chlorophyll (Chl) derivatives named Zn-Chl and H2 -Chl are examined as efficient hole-transporting layers (HTLs) for perovskite solar cells (PSCs) based on CH3 NH3 PbI3 (MAPbI3 ). The device structure here is ITO/SnO2 /MAPbI3 /Zn-Chl /H2 -Chl /Ag, which employs Zn-Chl /H2 -Chl as the bilayer HTL. Zn-Chl and H2 -Chl show different electronic absorptions, surface morphology, hole mobilities and energy levels due to their structural differences. The bilayer HTL realizes complementary performance of the Chl in each layer. The power conversion efficiency of the PSCs based on the bilayer Chl (Zn-Chl /H2 -Chl ) reaches 14.1% under standard AM1.5 illumination, which is higher than that of the device with monolayer Zn-Chl (11.9%) or H2 -Chl (0.16%) only. The bilayer HTL also exhibits better device stability. This is the first time that bilayer Chl has been used as a HTL in PSCs. It provides a promising method to enhance the performance of Chl-based PSCs.